Marketing communication and creative tourism: An analysis of the local destination management organization - Mafalda Gato; Álvaro Lopes Dias; Leandro Pereira; Renato J. Lopes da Costa; Rui Gonçalves (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Delivering a positive tourism experience is an expanding concern of destinations because of the growth of the tourism industry. The emergence of creative tourism has led to a continued necessity for local destination management organizations to pursue innovative and versatile strategies. This study aims to evaluate the organizational capabilities of local destination management organizations to promote a creative tourism context and develop related activities. The conceptual model was tested using a mixed-methods approach, combining a focus group with local destination management organizations with a quantitative study using multivariate statistical analysis through structural equational modeling. The findings showed that local destination management organizations ought to prioritize organizational culture by coordinating learning and effective knowledge training to strengthen marketing communication capabilities while focusing on potentiating their resources to develop the destination by implementing a local creative tourism destination, thereby generating value for a greater creative tourism local destination where tourists play an active role.
Keywords: 650; local destination management organization; destination tourism development; co-creation; organizational capabilities; marketing capabilities